Conception du dispositif collaboratif de prise de notes Unipad - Karine Bouchet (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Mobility and the integration of international students into the French higher education system is both an institutional and linguistic issue. How do French-as-a-foreign-language teachers and institutions adapt to the specific needs of allophone students within degree programs? How do they help allophone students follow lectures and take notes during these? The Unipad project at the Institut d’Études Politiques de Lyon (IEP), tested an innovative method to offer linguistic – but also methodological and socio-emotional – support during degree course lectures. This synchronous collaboration application between allophone and francophone students aims to support the note taking activity of international students and, more broadly, their inclusion in our institutions.